Decidualization Potency and Epigenetic Changes in Human Endometrial Origin Stem Cells During Propagation - Valatkaitė, Elvina; Baušytė, Raminta; Vitkevičienė, Aida; Ramašauskaitė, Diana; Navakauskienė, Rūta (Frontiers in Cell and Developmental Biology, 2021)
Human endometrium derived mesenchymal stem cells (EndSCs) offer a great promise for regenerative medicine and reproductive system disorders treatment methods based on cell therapy due to their broad differentiation potential and highly efficient proliferation. In our study we investigated the characteristics of EndSCs that were isolated from endometrium and menstrual blood that also has endometrial origin stem cells. Changes in gene and protein expression levels during long-term cultivation and decidualization potential were examined. The decidualization process was induced on early and late passages of EndSCs using dibutyryl cyclic-AMP (db-cAMP) and medroxyprogesterone acetate (MPA) agents. We demonstrated that after long-term cultivation of EndSCs the expression of typical mesenchymal stromal cell surface markers such as CD44, CD73, CD90, CD105 and perivascular marker CD146 remains at a similar level throughout long-term cultivation. Additionally, hematopoietic and endothelial markers CD34, CD45 were also tested, they were negative in all cases. Analyzed stem cells gene markers, such as OCT4, SOX2, NANOG, KLF4 showed similar expression in all passages of EndSCs. RT-qPCR results demonstrated that the expression of cell cycle control associated genes - CDK2, CCNA2, CCNE2, p21, p53 and Rb, among all groups was very similar. Expression of genes associated with senescence (ATM, JUND, TOP2A, MYC) was maintained at a similar level throughout passaging. In addition, Western blot analysis was used to assess changes in proteins‘ levels associated to epigenetics (EZH2, SUZ12, H3K27me3) and cell cycle control (cyclinE1, p53) during long-term cultivation. The levels of proteins associated with epigenetic changes were fluctuated slightly depending on the patient. Also, we demonstrated that in all induced EndSCs the expression of decidualization markers Prolactin (PRL), IGFBP1 and WNT4 was upregulated. In conclusion, we demonstrated successful decidualization of stem cells derived from two reproductive system resources: endometrium and menstrual blood by using db-cAMP and MPA regardless of the length of the stem cell passaging. According these findings, we suppose that endometrium derived stem cells and menstrual blood derived stem cells could have a potency not only for endometrium tissue regeneration, but, moreover could become a successful therapy for reproductive system disorders, including infertility or recurrent pregnancy loss.